5(3x+1)-2(5x+35)=0

Simple and best practice solution for 5(3x+1)-2(5x+35)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+1)-2(5x+35)=0 equation:


Simplifying
5(3x + 1) + -2(5x + 35) = 0

Reorder the terms:
5(1 + 3x) + -2(5x + 35) = 0
(1 * 5 + 3x * 5) + -2(5x + 35) = 0
(5 + 15x) + -2(5x + 35) = 0

Reorder the terms:
5 + 15x + -2(35 + 5x) = 0
5 + 15x + (35 * -2 + 5x * -2) = 0
5 + 15x + (-70 + -10x) = 0

Reorder the terms:
5 + -70 + 15x + -10x = 0

Combine like terms: 5 + -70 = -65
-65 + 15x + -10x = 0

Combine like terms: 15x + -10x = 5x
-65 + 5x = 0

Solving
-65 + 5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '65' to each side of the equation.
-65 + 65 + 5x = 0 + 65

Combine like terms: -65 + 65 = 0
0 + 5x = 0 + 65
5x = 0 + 65

Combine like terms: 0 + 65 = 65
5x = 65

Divide each side by '5'.
x = 13

Simplifying
x = 13

See similar equations:

| 3(-4)-2(-2*3)+9= | | -4(v-2)=-4(v-8)+8v | | -(x-2)=2-x | | 6+5m-4=9m+20-6m | | 3x+2x=54 | | -0.9x+2.65=-0.5x+5.45 | | 15+5n=6n | | 5x-20=15y+60 | | 2x-5=6x+4 | | 2y^2+17y+35= | | -4x+3=7x-8 | | 3x+8.13=2x | | 9x^2+60x=-100 | | 2x^2-4x+100=100 | | 15-5(1-1)=120-5 | | 4*2+10y=40 | | x^4+2x^3-x^2-x+1=0 | | 2(x-3)+x=3(x-5)+9 | | 6.5=10x+7.2 | | 2x+2(9x-9)-2x^2=13-28-3x^2+10 | | ax-3x+5=a+b | | X*(X-5)=176 | | 9(x-8)+4=9x+6 | | -4+3=7x-8 | | x^4-8x^3+15x^2-4x-20=0 | | 10x-5-14x+28=35-3x-2x | | x^4-4x^3+15x^2-4x-20=0 | | 5x+2=2x- 10 | | 8(2x-1)+2=12x+2(4x-5) | | m-4/8=-8 | | 30r^3+55r^2-175r= | | 10+4=2x+7 |

Equations solver categories